Cognitive Control in Russian–German Bilinguals - Festman, Julia; Münte, Thomas F. (Frontiers in Psychology, 2012)
Multilingual speakers are faced with the problem to keep their languages apart, but do so with interindividually varying success. Cognitive control abilities might be an important factor to explain such interindividual differences. Here we compare two late, balanced and highly proficient bilingual groups (mean age 24 years, L1 Russian, L2 German) which were established according to their language control abilities on a bilingual picture-naming task. One group had difficulties to remain in the instructed target language and switched unintentionally to the non-target language (“switchers”), whereas the other group rarely switched unintentionally (“non-switchers”). This group-specific behaviour could not be explained by language background, socio-cultural or demographic variables. Rather, the non-switchers also demonstrated a faster and better performance on four cognitive control tests (Tower of Hanoi, Ruff Figural Fluency Test, Divided Attention, Go/Nogo). In this paper we will focus on two additional cognitive tasks, the Wisconsin Card Sorting Test (WCST) and the Flanker task. Importantly, these two tasks require executive processing components for conflict monitoring and conflict resolution. Non-switchers outperformed switchers with regard to speed and accuracy, and were better at finding and applying the correct rules in the WCST. On the Flanker task, non-switchers performed faster and better on conflict trials and had a higher correction rate following an error. Event-related potential recordings furthermore revealed a smaller error-related negativity in the non-switchers. In sum, the non-switcher group consistently performed better and faster, in particular on high-conflict trials, probably due to better efficiency in dealing with conflict. They also demonstrated overall better self-monitoring abilities compared to switchers. We conclude that bilingual language performance, in particular switching behavior is related to performance on cognitive control tasks.